Fracture Resistance of Endodontically Retreated Roots After Retreatment Using Self-Adjusting File, Passive Ultrasonic Irrigation, Photon-Induced Photoacoustic Streaming, or Laser - Kamalak, Aliye; Uzun, Ismail; Arslan, Hakan; Keles, Ali; Doganay, Ezgi; Keskin, Cangul; Akcay, Merve (Mary Ann Liebert, Inc, 2016)
Objective: Additional cleaning techniques and devices are required to remove maximum amount of residual filling material, which might limit disinfection of root canal system during retreatment. This study aimed to compare fracture resistance of roots when self-adjusting file (SAF), photon-induced photoacoustic streaming (PIPS), passive ultrasonic irrigation (PUI), erbium-doped yttrium aluminum garnet (Er:YAG), or neodymium-doped yttrium aluminum garnet (Nd:YAG) lasers are applied following the use of retreatment files in endodontics. Materials and methods: A total of 117 human mandibular canine teeth of similar dimensions were selected and divided into nine groups (n=13). Aside from control, instrumented, and only-prepared groups, 91 teeth were remaining, of which 13 were assigned to the only-filling group and final 78 to retreatment, thus R-Endo file, R-Endo+SAF, R-Endo+PUI, R-Endo+Er:YAG laser, R-Endo+Nd:YAG laser, and R-Endo+PIPS. Results: The fracture strengths of the retreatment groups were lower than control, instrumented, and only-filling groups (p<0.05). There was no difference between the R-Endo group and additional retreatment procedure groups (p>0.05). Conclusions: Further cleaning methods using SAF, PIPS, Er:YAG laser, Nd:YAG laser, or PUI did not decrease the fracture resistance when compared with the R-Endo group.
Keywords: Rotary Niti Instruments; Removing Gutta-Percha; Filling Materials; Canal Dentin; Efficacy; Solvents; Teeth